Prasugrel hydrochloride for the treatment of sickle cell disease. (3rd July 2017) - Conran, Nicola; Rees, David C.
ABSTRACT: Introduction : Therapeutic options for sickle cell disease (SCD) are limited and, currently, only one drug (hydroxyurea) has FDA approval for the treatment of adult SCD. While this genetic disease is caused by hemoglobin polymerization, subsequent downstream events trigger platelet activation, vaso-occlusion and the disease's complex pathophysiology. Areas covered : The oral thienopyridine, prasugrel hydrochloride, irreversibly inhibits the P2Y12 receptors, inhibiting ADP-dependent platelet activation. We discuss recent clinical trials evaluating the pharmokinetics of prasugrel and its potential for use in SCD. Expert opinion : Prasugrel administration in SCD appears to be well tolerated and safe. However, although this drug modestly inhibits platelet activity in these patients, administration of prasugrel to a large group of children and adolescents for up to 24 months failed to convincingly reduce vaso-occlusive complications. Speculatively, prasugrel may be of occasional use for off-license purposes in patients unable or unwilling to take hydroxyurea (particularly in 12–17-year olds). Although there is currently no prospect of prasugrel being licensed for use in SCD, the success of on-going trials of other antiplatelet agents in SCD might lead to further trials of prasugrel in SCD.